The Macedonian state and party policy towards Albanians in Macedonia (1945–1991) - Stamova, Mariyana (Balcanica Posnaniensia. Acta et studia, 2010)
This study analyzes the development of the state and party policy of the Socialist Republic of Macedonia towards the Albanian minority during the period 1945–1991. At the end of World War II, with the establishment of Macedonian statehood within the Democratic Federal Yugoslavia, the Albanians were granted the status of a national minority with recognized cultural and educational rights. Nevertheless, their participation in socio-political life remained limited. The aim of the study is to trace the stages of this policy – from the initial integration and granted cultural freedoms to the increasing ethnopolitical tensions that led to deep contradictions by the end of the 20th century. The methodological approach is based on historical and political analysis supported by a wide range of sources, including party documents, constitutional acts, statistical data, and specialized scholarly literature. The analysis demonstrates that the demographic growth and cultural consolidation of the Albanian population, combined with the influence of developments in Kosovo, led to a gradual intensification of their political demands. After the Brioni Plenum (1966), the activity of Albanian intellectual and underground organizations increased, and during the 1980s political parties with an explicit ethnonational character emerged. In conclusion, the study emphasizes that the policy of the Socialist Republic of Macedonia towards the Albanians evolved from a form of cultural autonomy and controlled integration into a state of growing ethnic confrontation, which began to threaten the stability and territorial integrity of the country in the early 1990s. The research underlines the importance of the Albanian factor as a key element for understanding the internal political and inter-state dynamics within the post-Yugoslav context.